PENGARUH ASIMETRI INFORMASI TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEX (JII) TAHUN 2014-2018 - Wahyu Irawan; Muhamad Syaichu (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to determine the effect of information asymmetry on dividend policy in the Jakarta Islamic Index (JII). This research uses bid-ask spread, firm size, earnings forecast error, growth opportunity and insider ownership as independent variables and divided payout ratio as dependent variable. The number of samples in this study amounted to 8 companies which were determined using purposive sampling method. This study uses secondary data from the financial statements of companies listed in the Jakarta Islamic Index (JII) in 2014-2018. The research analysis technique used is multiple linear regression analysis, where previously the classical assumption test was carried out which included normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results showed that the firm size variable had a significant positive effect on the dividend payout ratio and earnings forecast error had a significant negative effect on the dividend payout ratio, while the bid-ask spread had an insignificant positive effect on the dividend payout ratio, growth opportunity and insider ownership had an insignificant negative effect on dividend payout ratio